Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1098/rsbl.2004.0222
|View full text |Cite
|
Sign up to set email alerts
|

Population variation in lateralized eye use in the poeciliid Brachyraphis episcopi

Abstract: Differential use of each hemisphere of the brain for specif ic tasks is a widespread phenomenon that appears to have arisen in the early history of tetrapod lineage. Despite a high degree of conformity in the development of lateralization among the tetrapods, some variation exists. The mechanisms underlying this variation remain largely unresolved. We exposed f ish from regions of high and low predation pressure to a series of visual experiences, including viewing an empty compartment, a novel object and a liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 22 publications
4
112
2
Order By: Relevance
“…A study of 16 species of fish found that all shoaling species showed population-level lateralization of predator evasion behaviour, whereas non-shoaling species tended to have individual but not population lateralization (Bisazza et al 2000). A field study reported in the poeciliid fish Brachyraphis episcopi that individuals from high-predation populations were more lateralized than their lowpredation counterparts (Brown et al 2004). The authors suggested that in a population with a high predation pressure, selection has favoured lateralized fish because they are better able to cope with two simultaneous tasks, such as foraging and predator vigilance.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 16 species of fish found that all shoaling species showed population-level lateralization of predator evasion behaviour, whereas non-shoaling species tended to have individual but not population lateralization (Bisazza et al 2000). A field study reported in the poeciliid fish Brachyraphis episcopi that individuals from high-predation populations were more lateralized than their lowpredation counterparts (Brown et al 2004). The authors suggested that in a population with a high predation pressure, selection has favoured lateralized fish because they are better able to cope with two simultaneous tasks, such as foraging and predator vigilance.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of salamander eggs to predator odour induces more efficient anti-predatory strategies in post-hatching larvae (reduced activity and preference for vegetated habitats [38]). In fish, lateralized behaviour patterns fluctuate between populations of the same species exposed to differing levels of predation pressure [10]. In poeciliid fish, females from highpredation areas display stronger side-turning biases, when faced with a novel object than those from low-predation areas [11].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated opercula beat rate is a measure commonly used to infer a physiologically stressed state in fish (e.g. Lucas et al 1993, Brown et al 2004. Changes in opercula beat rate are a sensitive response to disturbance, but it should be recognised that they do not always reflect the severity of the stimulus (Baretto & Volpato 2004).…”
Section: Nociception and The Effects Of Noxious Stimuli In Teleost Fishmentioning
confidence: 99%